First Record, Occurrence And Distribution Of Entomopathogens In Populations Of The European Cockchafer, Melolontha Melolontha (Coleoptera: Scarabaeidae) In Turkey - Yaman, Mustafa; Algi, Gonul; Guner, Beyza Gonca; Erturk, Omer; Unal, Sabri; Radek, Renate (Aperta, 2016)
In the present study, the first record, occurrence and distribution of three different pathogens: two protistan pathogens; a coccidian and a neogregarine, and an entomopoxvirus from the European cockchafer, Melolontha melolontha L. (Coleoptera: Scarabaeidae) are given. A neogregarine pathogen was recorded for the first time from M. melolontha populations. A coccidian pathogen, Adelina melolonthae was recorded for the first time for Turkey. An entomopoxvirus was recorded from a new locality, Kocaeli in Turkey, The infections caused by pathogens were observed in the haemolymph and fat body of the adults and larvae. The occurrence and distribution of these pathogens in the M. melolontha populations are also presented.